Cost-Effectiveness of Fetal Fibronectin Testing to Predict Preterm Birth in Pregnant Women with Symptoms of Premature Labour - Dina Abushanab (10696501) (2023)
Objective To evaluate the cost-effectiveness of fetal fibronectin (fFN) versus no-fFN testing to detect true preterm labor in qualifying women with preterm labor symptoms at risk for preterm birth. Design Retrospective cost-effectiveness analysis. Method Retrospective cost-effectiveness analysis of fFN versus no-fFN testing to detect preterm labor at Women's Wellness and Research Center (WWRC), Qatar, was conducted. Clinical data of pregnant women were obtained from Cerner medical records from 2017-2022, whereas cost data were obtained from the pharmacy as well as finance and costing departments of HMC. The model included direct medical costs; thus, the perspective of HMC was adopted. Included resources were (i) fFN testing use, (ii) medications use (i.e. tocolytic, steroid), (iii) diagnostics and laboratory tests received during hospitalization (iv) management of adverse drug events, and (v) hospital stay excluding other resource costs. A decision analytic model was constructed to follow possible consequences of fFN or no-fFN testing. Primary end points were the success rate in prolonging delivery, defined as delivery at 48 hours following receiving one cycle of atosiban and antenatal corticosteroids from initial presentation to the emergency department as well as overall direct medical cost of management. Study population of 200 pregnant women between 24-34 weeks of gestational age at risk for preterm birth was used. Sensitivity analysis was conducted to enhance robustness of conclusions against input uncertainties and to increase generalizability of results. Results Our preliminary data showed that hundred women were available for inclusion in each study group. The fFN group had 12% success rate in prolonging delivery at 48 hours following receiving one cycle of atosiban and antenatal corticosteroids compared to 5% with no-fFN group, [risk ratio (RR)= 0.93; 95% CI, 0.85 to 1.01; P = 0.08]. fFN testing was estimated to dominate the no-fFN testing group, at a cost saving of QAR 236,702 (US$ 64,850), with total healthcare costs of QAR 171,623 (US$ 47,020) versus QAR 408,325 (US$ 111,870), respectively. Sensitivity analysis confirmed robustness of conclusions. Conclusions To the best of our knowledge, this is the first cost-effectiveness evaluation in the literature that provides new insights into the benefits of fFN versus no-fFN testing to detect preterm labor in women between 24-34 weeks of gestational age with preterm labor symptoms at risk for preterm birth. The fFN testing might be associated with prolonging delivery at 48 hours at a considerably lower cost. The study findings support recent trends in favor of fFN use.